Пародия на героя классической драмы в пьесах Николая Коляды - Anna Maroń (Studia Rossica Posnaniensia)
The article is devoted to studying the recent phenomenon concerning a new model of the hero in Russian dramaturgy based on the example of Nikolai Kolada’s plays. All of the characters are deprived of their traditional features and they function as language constructs, discursive practices or a “Voice”.